Propriedades físicas e indicador de qualidade de um latossolo vermelho submetido a diferentes sistemas de uso e manejo - Netto, Antonio Angelotti; Fernandes, Edemo João [UNESP]; Centurion, José Frederico [UNESP] (My University, 2007)
The conventional system for soil management and preparation has the intensive mechanization as its basic principle and that changes soil properties, especially physical ones, faster and significantly. This study aimed to obtain and compare physical properties such as distribution of particle sizes, density, distribution of pore sizes, curves of water retention and degradation index of a Red Latosol, under intensive cultivation and no-cultivation for six years. Soil samples were collected at depths of 0.1, 0.2, 0.3, 0.4, 0.6, 0.8 and 1.0 m. There was a clay increment as a result of cultivated soil increase. The no-till soil density decreased as depth increased; however, in the arable layer (0.3 m) of the cultivated soil, the opposite was verified. The largest volume of pores was verified in the cultivated soil, especially in the superficial layers. In the smallest applied tension (0.001 MPa), the cultivated soil retained more water; however, starting from 0.033 MPa, the highest humidity values occurred in the no-till soil. The highest degradation index was observed at a depth of 0.1 m in no-till soil. However, that value was superior (0.020) to what is physically considered very poor soil.
Physical properties and quality indicator of a red latosol under different use and management systems
Keywords: Bulk density; Degradation index; Non-cultivated; Porosity; Water retention; Atmospheric humidity; Cultivation; Particle size; Pore size; Soil moisture; Soils; bulk density; particle size; physical property; porosity; red soil; soil degradation; soil management; soil quality; soil water; water retention